Manners of resistance symbolic defiance of colonial authority in nineteenth century Philippines - Santiago, Fernando A. Jr. (2015)
Several accounts of ride and vulgar behavior that annoyed Westerners are mentioned in the nineteenth century documents on the Philippines. Filipino "bad manners" have been cited as proof of the inferiority of the race and used to underrate their intelligence. If Filipinos are to be understood in their own terms, there lies the possibility that the incidents of rudeness mentioned in the historical accounts were actually acts of defiance against colonial authority, the prospect that bad manners were forms of everyday resistance. The study sheds light on acts that made Filipinos rude, deceitful, distrustful, clumsy and insolent; and treat them as symbolic defiance of colonial authority on account of the traditions, ethics, cultural framework and emotionalism of Filipinos.

The objective of the study is to highlight everyday resistance in Philippine history. While historical studies have dealt with the subject matter, such works have been inadequate in making the phenomenon part of the people's historical consciousness. In continually giving attention to an overlooked aspect of Filipino resistance, the public may eventually acknowledge past actions that have been largely ignored. The present study is meant to bring into higher light the actions of numerous nameless individuals who like the "great men" of history also opposed colonial authority. The study is also meant to broaden awareness of the range by which resistance has been expressed in the Philippines.
Keywords: Manners and customs; Offensive behavior; Philippines -- Literary collections -- 19th century; Philippines -- Social life and customs; Philippines -- Culture